2021
DOI: 10.1097/ogx.0000000000000912
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal Estrogen Therapy Is Associated With Increased Lactobacillus in the Urine of Postmenopausal Women With Overactive Bladder Symptoms

Abstract: Introduction-Previous work has shown that the vaginal microbiome decreases in Lactobacilluspredominance and becomes more diverse following menopause. It has also been shown that estrogen therapy restores Lactobacillus-dominance in the vagina, and that topical estrogen is associated with OAB symptom improvement. We now know that the bladder contains a unique microbiome, and increased bladder microbiome diversity is associated with OAB. However, there is no understanding of how quickly each pelvic floor microbio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 28 publications
2
7
0
Order By: Relevance
“…Our analysis of cohort-associated metadata found a strong link between EHT use and the presence of Lactobacillus in the urobiome of non-infected patients. These observations support those made by Thomas-White et al and are of particular interest to research endeavors seeking to identify possible UTI-protective members of the urinary and urogenital tract microbial communities (Thomas-White et al, 2020). Lactobacilli control the local chemical environment of the vagina and are responsible for not only maintaining an acidic pH, but also secrete large amounts of the antimicrobial D (-) lactate isomer (Amabebe and Anumba, 2018).…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Our analysis of cohort-associated metadata found a strong link between EHT use and the presence of Lactobacillus in the urobiome of non-infected patients. These observations support those made by Thomas-White et al and are of particular interest to research endeavors seeking to identify possible UTI-protective members of the urinary and urogenital tract microbial communities (Thomas-White et al, 2020). Lactobacilli control the local chemical environment of the vagina and are responsible for not only maintaining an acidic pH, but also secrete large amounts of the antimicrobial D (-) lactate isomer (Amabebe and Anumba, 2018).…”
Section: Discussionsupporting
confidence: 85%
“…In a 2021 report, Anglim et al found no difference in urinary lactobacilli among postmenopausal women with and without rUTI taking vaginal EHT compared to baseline controls (Anglim et al, 2021). However, Thomas-White et al reported a significant enrichment of lactobacilli in the bladders of postmenopausal women with overactive bladder symptoms using vaginal EHT (Thomas-White et al, 2020). These results along with our report suggest nuances in the association between urinary lactobacilli and EHT that merit future mechanistic research.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…If indeed an underlying dysbiosis of the urinary bladder and vaginal microbiome are believed to correspond with lower urinary tract symptomatology, which has been suggested in previous studies, then one would expect to also see more changes in the bacterial community for more symptomatic women. This was the case in a study by Thomas-White et al 18 of postmenopausal women with overactive bladder symptoms, showing an increase in urinary bladder Lactobacillus after vaginal estrogen supplementation, which correlated to symptom improvement. Another study by Komesu et al 23 did not find overall differences in urinary bladder Lactobacillus predominance in women with and without mixed urinary incontinence, although subgroup analysis suggested that in women younger than 51 years, a decreased Lactobacillus predominance was associated with mixed urinary incontinence.…”
Section: Discussionmentioning
confidence: 71%